Heresy and borders in the twentieth century - Jakubowicz, Karina; Dickins, Robert (Routledge, 2021)
Introduction / Karina Jakubowicz & Robert Dickins -- The concrescence of dissent : Whitehead as religious, scientific, philosophic heretic / Peter Sjöstedt-H -- Edward Carpenter and early modernist heresy / Henry Mead -- Christian occultism : Charles Williams and the erosion of heresy / Aren Roukema -- 'Spilt religion' : heresy in classical modernism / Christos Hadjiyiannis -- Heresy in paradise : literary modernism and the Genesis myth / Karina Jakubowicz -- Experimental heresies : LSD and Christianity in Britain / Robert Dickins -- The tyranny of cool : orthodoxy, heresy, and the 1960s counterculture / Guy Stevenson -- Immanent eschaton : Discordian and Deleuzian dissimulations of the goddess / Benjamin J. Austin -- Representations of ritual in twentieth century concert dance / Moe Dodson -- Blasphemy, heresy and liberalism in late twentieth century Britain / Piers Benn -- Afterword / Gregory Erickson and Suzanne Hobson.